Differential regulation of the release of tumor necrosis factor-alpha and of eicosanoids by mast cells in rat airways after antigen challenge - Trezena, A. G.; da Silva, Z. L.; Oliveira, R. M.; Damazo, A. S.; Straus, A. H.; Takahashi, H. K.; Oliani, S. M.; de Lima, W. T. (Carfax Publishing, 2003)
Background: Rat trachea display a differential topographical distribution of connective tissue mast cells (CTMC) and mucosal mast cells (MMC) that may imply regional differences in the release of allergic mediators such as tumor necrosis factor-alpha (TNF-alpha) and eicosanoids.Aim: To evaluate the role of CTMC and MMC for release of TNF-alpha and eicosanoids after allergenic challenge in distinct segments of rat trachea.Materials and methods: Proximal trachea ( PT) and distal trachea (DT) from ovalbumin (OVA)-sensitized rats, treated or not with compound 48/80 ( 48/80) or dexamethasone, were incubated in culture medium. After OVA challenge, aliquots were collected to study release of TNF-alpha and eicosanoids.Results: Release of TNF-alpha by PT upon OVA challenge peaked at 90 min and decayed at 6 and 24 h. Release from DT peaked at 30-90 min and decayed 6 and 24 h later. When CTMC were depleted with 48/80, OVA challenge exacerbated the TNF-alpha release by PT at all time intervals, while DT exacerbated TNF-alpha levels 6 and 24 h later only. Dexamethasone reduced TNF-alpha production after 90 min of OVA challenge in PT and at 3 and 6h in DT. OVA challenge increased prostaglandin D-2 in DT and leukotriene B-4 in both segments but did not modify prostaglandin E-2 and leukotriene C-4 release.Conclusion: OVA challenge induces TNF-alpha release from MMC, which is negatively regulated by CTMC. The profile of TNF-alpha and eicosanoids depends on the time after OVA challenge and of the tracheal segment considered.
Keywords: TNF; eicosanoids; Mast cells; airways; asthma; rat